Is HCV Genotyping Cost-Effective Even When the Prevalences of Genotypes 2 and 3 are Low? - (:unkn) unknown (H G E UPDATE MEDICAL PUBLISHING S A, 2009)
Background/Aims: The management of chronic hepatitis C virus (HCV) infection is costly. Genotyping determines the indication, probability of response.. and duration of treatment and the dose of ribavirin. Although genotyping is accepted cost-effective, the cost of genotyping in all of the patients to find out a minority may offset the gain. The present study aimed; 1) to determine the frequency rate of HCV genotypes and 2) to compare the cost of HCV treatment tailored according to the genotype versus that planned supposing it to be genotype 1. Methodology: Six centers were included into the study. Name, age, genotype, and serotype of each patient were entered. For genotyping, HCV-RNA was extracted by acid-guanidium-phenol-chloroform method. Cost of genotyping, HCV-RNA studies and the treatment with pegylated interferon and ribavirin was estimated. The cost was deter-mined according to two scenarios: A) To manage patients as if all had genotypes other than 2-3. B) To manage them after determining the genotype. The management was assumed to be made by current guidelines. Results: The data of 834 patients were analyzed: Genotype1 was predominant: 730(87.5%). The rest was composed of G2:26(3.1%), G3:26(3.1%), G4:14(1.7%), mixed: 13(1.6%), undetermined: 25(3%). The cost of approach A (for 100 patients) was 1,718,200 USD; that of approach B (for 100 patients) was 1,671,900 USD. With genotype targeted therapy, every 100 patient would save 46,300 USD. Conclusions: The prevalent genotype in our country is genotype1. The sum of genotypes 2 and 3 corresponds to 6%. Genotyping HCV and tailoring the treatment thereafter are cost-effective even in the countries where prevalence of these genotypes is low.
Keywords: Hepatitis C; Genotyping; Cost-effectiveness; HEPATITIS-C VIRUS; INTERFERON-ALPHA-2B PLUS RIBAVIRIN; INITIAL TREATMENT; RANDOMIZED-TRIAL; TURKISH PATIENTS; INFECTION; STEATOSIS